2023
DOI: 10.1007/s00277-023-05087-8
|View full text |Cite
|
Sign up to set email alerts
|

Different treatment strategies versus a common standard arm (CSA) in patients with newly diagnosed AML over the age of 60 years: a randomized German inter-group study

Abstract: A randomized inter-group trial comparing more intensive treatment strategies to a common standard arm 3 + 7 (CSA) was conducted in patients with non-M3 AML. Untreated patients ≥ 60 years were allocated to the CSA (n = 132) or to the study group arms (n = 1154) of the AMLCG (TAD/HAM versus HAM/HAM ± G-CSF followed by TAD and maintenance) and the OSHO (intermediate-dose ara-C/mitoxantrone followed by ara-C/mitoxantrone). Median age of the 1147 eligible patients was 69 (range 60–87) years. CR/CRi status at 90 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…61 Results showed that compared with the 7 + 3 regimen, there were no significant differences in CR, event-free survival, overall survival, and relapse-free survival. 61…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…61 Results showed that compared with the 7 + 3 regimen, there were no significant differences in CR, event-free survival, overall survival, and relapse-free survival. 61…”
Section: Discussionmentioning
confidence: 91%
“…The study examined patients 60 years and older who were exposed to various intensive chemotherapy regimens versus the 7 1 3 regimen. 61 Results showed that compared with the 7 1 3 regimen, there were no significant differences in CR, eventfree survival, overall survival, and relapse-free survival. 61 Most of the selected recommendations gained panel endorsement, with exceptions in the incorporation of cladribine to the 7 1 3 regimen.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations